2015
DOI: 10.1016/j.chiabu.2015.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Perpetrators and context of child sexual abuse in Kenya

Abstract: Child sexual abuse (CSA) interventions draw from a better understanding of the context of CSA. A survey on violence before age 18 was conducted among respondents aged 13–17 and 18–24 years. Among females (13–17), the key perpetrators of unwanted sexual touching (UST) were friends/classmates (27.0%) and among males, intimate partners (IP) (35.9%). The first incident of UST among females occurred while traveling on foot (33.0%) and among males, in the respondent’s home (29.1%). Among females (13–17), the key per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
19
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 15 publications
8
19
0
4
Order By: Relevance
“…Our findings were similar to those of two nationally representative studies of childhood sexual violence in Kenya. In one study, researchers found rates of 23.1% (girls) and 11.8% boys [39]. Results of a second study showed rates of 14.8% of sexual violence against Kenyan boys before age 18 in 3 countries including Kenya [40].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings were similar to those of two nationally representative studies of childhood sexual violence in Kenya. In one study, researchers found rates of 23.1% (girls) and 11.8% boys [39]. Results of a second study showed rates of 14.8% of sexual violence against Kenyan boys before age 18 in 3 countries including Kenya [40].…”
Section: Discussionmentioning
confidence: 99%
“…Estos resultados son consistentes con los de estudios de encuestas. Así Mwangi y col. [27], Breiding y col. [28] y Reza y col. [29] mostraron como población vulnerable a los menores de edad, adolescentes y jóvenes; del sexo femenino y con bajo nivel de escolaridad.…”
Section: Discussionunclassified
“…Los resultados mostraron que más de la mitad (52,9%) de su población de estudio, había consumido menos de tres comidas el día anterior y el 34,8% (1.287/3.706) eran menores trabajadores que no estudiaban. Así mismo Mwangi y col. [27] y Breiding y col. [28] reportaron Caracterización de los casos de violencia sexual atendidos en dos instituciones prestadoras de servicios de salud del municipio de Palmira-Valle Del Cauca, Colombia. prevalencia en menores de edad que se desarrollan en hogares con bajos ingresos, reflejado en bajo nivel de escolaridad.…”
Section: Discussionunclassified
See 2 more Smart Citations